INTEGRATED GEOELECTRICAL AND HYDRAULIC CHARACTERIZATION OF BASEMENT AQUIFERS FOR GROUNDWATER EXPLORATION IN KUJE DISTRICT, ABUJA, NIGERIA - Ikuemonisan, Michael Soga; Kizito, Musa Ojochenemi; Akpah, Fabian Apeh; Jimoh, Jacob Bolaji (FUDMA JOURNAL OF SCIENCES, 2025)
Basement complex terrain is typically made of hard rocks with limited porosity and permeability, which pose a serious challenge to the groundwater system and resulted in water scarcity even in the study area. Twenty-nine Vertical Electrical Soundings and Dar-Zarrouk parameters were analyzed to delineate aquifer systems. Topsoil, lateritic clay, weathered basement, fractured basement, and fresh basement comprised the multi-layered subsurface structure that was shown by the VES curves. Typical subsurface sequences with alternating resistive and conductive layers reveal weathered or fractured aquifers typical of basement terrains. These curve types include KH-type (41.38%), HA-type (24.15%), KHA (10.35%) and QH (6.90%), H, HK, AK, and HAA (≤3.45%). It was determined that the principal aquifers were the weathered and fractured basement layers, with thicknesses ranging from 3 to 52m and resistivity values between 38.0 and 2429.3Ωm. Transverse resistance (250–43,934Ωm²), hydraulic conductivity (0.3–13m/day), longitudinal conductance (0.01–0.32S), and transmissivity (3.5–161m²/day) were among the Dar Zarrouk parameters that showed significant spatial variability. The northeastern sector (Kuje central) had high-yield zones due to favorable permeability and thickness, while the northwestern and southwestern areas (Chibiri and Godaji area) had limited groundwater potential. The aquifers' rate of pollution is poor to moderate. These findings provide a framework for sustainable groundwater exploration in basement complex terrains.
Keywords: Groundwater; Aquifer Properties; Vulnerability; Abuja; Central Nigeria